(3TQM QSGdI aj EYLGR GdbQBfs - (3eLghds
(3ChdgG (B:s
(3JHOC CKfGA HGH GdJTHjg , Hbhdg (B: (3WQjb GdHdGZI Mjf THg TjFkG HTF dGJaGhJ HjfgeG , bdfG Ef gPg GdJTHjgGJ eeG cGfJ GdYQH JJOGhdI HCdSfJgG hdjS gh eeG EbJVHg GdTGYQ ai TYQg s
(3BNQgG (B:s
(3hdjS ajeG ChQO ai gPG GdHGH GdCNjQ TF jMJGL dg Edi ESJFfGa JaSjQ Je TQM GdQSGdI GdMeO ddg QH GdYGdejf hUdi Gddg Ydi QShdg eMeO hBdg GdWjHjf GdWGgQjf s
(3fSNI fajSI LOkG hbOjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs